Survey of side channel attack on encrypted network traffic - Ding LI; Yuefei ZHU; Bin LU; Wei LIN (网络与信息安全学报)
By analyzing and extracting information such as packet size and timing leaked during Web application communication, side channel attack on encrypted network traffic is able to recognize users' identity and behavior and even restore the original data entered by users.A model of side channel attack on encrypted network traffic according to information theory was developed.Based on the unified model, the methods and results of representative attacks such as fingerprinting attacks, keystroke attacks and speech attacks were analyzed in detail.Furthermore, defense methods of hiding packet size and timing information were discussed.At last, possible research directions were prospected with the frontiers of technology development.